Family business leaders' attitude toward conflict and next generation talent pool - Salim, Linda; Mohd Shariff, Mohd Noor; Ahmad Arshad, Darwina; Surya Saputra, Ruswiati (2016)
Family business leaders approaching succession are known to deal with overwhelming issues of management and conflicts. This ongoing study proposes that leaders' attitude when approaching conflict influences the size of next generation talent pool. Thus, determining its chance at survival.